Tanjung Perak Port Solid Waste Composting using Black Soldier Fly Method - Ulvi Pri Astuti; Vivin Setiani; Mirna Apriani; Tanti Utami Dewi; Nyoto Sulistiyo (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2022)
One of the supporting facilities for operational activities at the Tanjung Perak Port is the existence of adequate green open spaces. The type of plant that is widely planted is the Angsana tree. Since 2018, this port has had an innovation to reuse waste from trimming activities to become compost, but the results are not optimal because there is still a lot of compost in the form of whole leaves. In this research, the composting method will be tested using Black Soldier Fly larvae and local microorganisms from banana hump. Compost material in the form of the waste of Angsana leaves is mixed with the waste of mackerel fish which comes from processing activities of mackerel fish food. Variations were made with different feeding regimes for Black Soldier Fly larvae, namely 3 weekly, daily, and weekly with dose of local microorganism banana hump as much as 15 mL/kg. The results of composting showed that the variations of feeding regime have significant effect for compost quality.